2014
DOI: 10.1186/1477-7517-11-21
|View full text |Cite
|
Sign up to set email alerts
|

Substance use and associated factors among preparatory school students in Bale Zone, Oromia Regional State, Southeast Ethiopia

Abstract: IntroductionThe use of cigarettes, alcohol, khat, and other substances is a worldwide threat which especially affects young people and which is also common among the youth of Ethiopia. However, its prevalence and associated factors have not been addressed well yet. Thus, this study aimed to assess the prevalence and associated factors of substance use among preparatory school students in Bale Zone, Oromia Regional State, Southeast Ethiopia.MethodsAn institutional-based cross-sectional study was conducted among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
59
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 10 publications
12
59
2
Order By: Relevance
“…respectively. This finding was consistent with other studies conducted among preparatory school students in Bale Zone 23.6% [14], high school students in Harare town 24.2% [17] and in Dire Dawa 27.7% [11]. This consistency may be due to cultural and age group similarity between the study populations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…respectively. This finding was consistent with other studies conducted among preparatory school students in Bale Zone 23.6% [14], high school students in Harare town 24.2% [17] and in Dire Dawa 27.7% [11]. This consistency may be due to cultural and age group similarity between the study populations.…”
Section: Discussionsupporting
confidence: 92%
“…Muslim students were 6.390 [AOR 95% CI= (1.903-21.460)] times more likely to chew khat than other religious followers. This is also consistent with the finding of other studies in Ethiopia and abroad [13][14][15]19]. This association might be due to the fact that khat hewing practice has traditionally been confined to Muslim populations, and also it might be due to the religious dogma.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Paternal substance use in general has been shown to be associated with higher odds of substance use among high school students in southeast Ethiopia54 and among adolescents elsewhere 55. Previous studies have also shown paternal alcohol abuse to be significantly associated with alcohol abuse among adolescents and young adults 5658.…”
Section: Discussionmentioning
confidence: 96%
“…In this study area, the most commonly used substance were alcohol 50 (13.4%), khat 35(9.4%) & tobacco29 (7.8%). This is also lower than nding in Dire Dawa secondary school and Ginnir town preparatory school , Bale zone (11,12). This difference may be due to difference in stud area where there is availability of chat and otter substance.…”
Section: Discussionmentioning
confidence: 61%